FACTORS RELATED TO SAFE DRIVING BEHAVIOR IN STUDENTS AT SMK MUHAMMADIYAH 1 PEKANBARU - Syifa Rahmah Fadila; Januar Ariyanto; Dadang Herdiansyah; Andriyani (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Safety Riding is a way of driving that is safe and comfortable for a rider against other riders. Based on data from the Pekanbaru Police Traffic Unit in the last 3 years (2018-2020) there have been 576 traffic accidents due to safety riding issues such as not using personal protective equipment, not obeying traffic signs, driving at high speed, and driving in underage. motor vehicle. good traffic awareness and safe driving behavior are needed for the community, especially among teenagers, such as in Pekanbaru. This study was to determine the relationship between knowledge level and safe driving behavior (safety riding) in class XII students at SMK Muhammadiyah 1 Pekanbaru. This research is a quantitative research using analytic methods using a cross sectional approach which will take a sample of 216 students by using the two proportions difference hypothesis test. Analysis with chi square = 0,05.  Data collection used  a  questionnaire   with    ethical   number No.10.169.B/KEPK- FKMUMJ/VI/2023. Related variables include knowledge variable with p-value 0.021, attitude variable with p-value 0.010, gender variable with p-value 0.006, SIM ownership variable with p-value 0.044, driving period variable with p-value 0.005, distance variable travel with a p-value of 0.009. while the variables that have no relationship include, the age variable with a p-value of 0.864. The level of knowledge related to safe driving behavior is knowledge, attitude, gender, driving license ownership, driving period, and mileage. For Pekanbaru Police, they should pay more attention to and provide education to schools about driving safety from an early age so that it is hoped that this will reduce the risk of accidents in young adults because they have received knowledge from an early age.